The Influence of Tecnology Adaptation and Market Orientation on Business Performance of BPR in Karanganyar with Competitive Advantage as the Mediation - Susanto Tanggono; Maria Y.D. Hayu Agustini (Journal of Management and Business Environment (JMBE), 2022)
The study addresses competition problems experienced by BPRs in Kabupaten Karanganyar. The competition from other financial instutions in particularly fintech has led the BPRs to experience a decline in particularly credit performance. The purpose of this study was to analyze the effect of new technology adaptation and market orientation on competitive advantage and business performance of BPRs in Kabupaten Karanganyar. The study selected executive officers and directors of 12 BPRs available in Kabupaten Karanganyar using purposive sampling. Those have worked for at least 3 years for the BPR were selected as the respondents and this resulted in 54 respondents. Data was collected using questionnaire and was analyzed using Structural Equation Modeling-PLS. The analysis indicates that new technology adaptation and market orientation have positive and significant effect on competitive advantage. New technology adaptation has direct effect on business performance, but market orientation shows indirect effect on business performance through competitive advantage. Competitive advantage is only proven to mediate the effect of market orientation on business performance and unable to mediate the effect of adaptation new technology on business performance.